British wind farm ESS attachments: curtailment reduction vs. price arbitrage - Atherton, John (2024)
Energy storage systems (ESSs) are a potential solution to the rising issues of electricity price volatility and curtailment of British wind energy. This study performs an extensive and knowledge graph supported investigation into 47 potential wind farm ESS co-location sites. While all ESSs achieved payback due primarily to price arbitrage, results indicate English/Welsh sites (typically with offshore wind) had quicker payback times owing to higher capacity factors presenting more opportunistic charging times. Conversely, while batteries co-located with Scottish wind farms attained slower payback times, they accomplished greater curtailment reductions, which could be used to displace marginal selling from generally fossil fuelled sources.